Different Aspects Of Production Of Thermolysin-Like Protease From Thermoactinomyces Thalpophilus - D.R MAJUMDER,; P.P KANEKAR, (International Journal of Pharma and Bio Sciences, 2012)
Thermoactinomyces thalpophilus (Gene Bank accession number EF 397000) isolated from the waters of a thermal spring situated in Western Ghats, Maharashtra, India was found to be a potent producer of thermolysin-like protease (TLP). TLP was capable of bringing about condensation/ biotransformation of two amino acids, viz. Z-L-aspartic acid and L-phenylalanine methyl ester into aspartame, which is an artificial, non-saccharide sweetener used as a sugar substitute in some foods and beverages. The maximum yield 181 U/ml/min was obtained at 55oC in glucose yeast extract medium(pH 7.2) containing CaCl2 ( 0.2 % w/v) with an inoculum size of 0.5% v/v after 18 hours incubation under shake-culture conditions (130 rpm)